1988
DOI: 10.1152/ajprenal.1988.255.5.f885
|View full text |Cite
|
Sign up to set email alerts
|

Cl(-)-dependent ATP-driven H+ transport in rabbit renal cortical endosomes

Abstract: An endosomal fraction isolated from rabbit renal cortex by a novel, fast, and simple procedure was enriched in ATP-dependent H+ pumping that was oligomycin insensitive but was inhibited by dicyclohexylcarbodiimide (DCCD), N-ethylmaleimide (NEM), Zn2+, Hg2+, diethylstilbestrol, mersalyl, and 4-chloro-7-nitrobenzo-2-oxa-1,3-diazole. No substantial Na+-H+ exchange was detected. Electrogenicity of the pump was demonstrated using [14C]-SCN-. In addition, these membranes featured ATP-dependent Cl- flux. The ATP-driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
1

Year Published

1990
1990
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 0 publications
2
50
0
1
Order By: Relevance
“…The role of chloride channels in H + -ATPase function is not explained only by the establishment or dissipation of a potential difference across cellular and intracellular membranes, but some evidence has supported a direct, specific role of Cl -in stimulating H + -ATPase activity (16). Kaunitz et al (17) have shown that acidification of microsomes from the rat renal medulla depends on chloride channels.…”
Section: General Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of chloride channels in H + -ATPase function is not explained only by the establishment or dissipation of a potential difference across cellular and intracellular membranes, but some evidence has supported a direct, specific role of Cl -in stimulating H + -ATPase activity (16). Kaunitz et al (17) have shown that acidification of microsomes from the rat renal medulla depends on chloride channels.…”
Section: General Considerationsmentioning
confidence: 99%
“…In the kidney, the role of Cl -channels in regulating H + -ATPase activity has been studied in endosomal fractions (16,27,29), brush border membrane vesicles (3) as well as in apical membranes of renal tubules (10,(30)(31)(32).…”
Section: Kidneymentioning
confidence: 99%
“…In view of evidence that the activity of H ϩ -ATPase is affected by Cl Ϫ (2,11,12), experiments were carried out in which either Cl Ϫ was removed from the perfusion fluid (Fig. 2B) or AII was added in the presence of the potent anion channel blocker NPPB (see Fig.…”
Section: Namentioning
confidence: 99%
“…Two mechanisms have been suggested to account for the Cl Ϫ dependence of H ϩ -ATPase activity. First, Cl Ϫ ions are necessary as cotransported anions to maintain electric neutrality during H ϩ ion transport (12,20,(22)(23)(24). The observation that the deletion of Cl Ϫ and exposure to Cl Ϫ channel blockers abolishes AII-stimulated pH recovery after deletion of Na ϩ supports this view.…”
mentioning
confidence: 97%
“…It has been shown that the presence of ATP activates not only H + -ATPase, but also the Cl -channels connected to it (10); and even after dissipating the PD across endosome membranes with valinomycin, the ATPase still depends on the presence of Cl - (3).…”
Section: Introductionmentioning
confidence: 99%